Síntese, caracterização e avaliação da atividade biológica de derivados Fluorados de Chalconas - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Chalcones form the core of many α, β-unsaturated aromatics that form the core of many aromatics. They are the biogenetic precursors of flavonoids and isoflavonoids found abundantly in plants. The chalcone class has attracted much interest not only from a biosynthetic perspective, but also because of its broad biological activities. In this context, the present work of synthesis and characterization of chalcone components (9a and 9b), evaluation of the effect of chalcones (B1, C1, C2 and C4) in the formation of biofilm isolated by clinicians of Pseudomonas aeruginosa, in them screening of antitumor activity through the potato disk bioassay technique of results B1 and B2 and on the toxicity of the four results of Chalconas in Artemia salina. The pyrazole compounds 1-(5-(2,6-difluorophenyl)-4,5-dihydro-3-p-tolylpyrazol-1- yl)ethenone (9a) and 1-(5-(2,6-difluorophenyl) ) )-3-(furan-2-yl)-4,5-dihydropyrazol-1-yl) synthesethanone (9b) were from the single chalcones by the Claisen-Schmidt type aldol reaction, using some aromatic reactions and aromatic ketones, then they were characterized by spectrometry in the infrared region (IR), magnetic mass spectrometry (NMR) and magnetic mass spectrometry (NMR) of 1H and 13C having their biologicalactivities. Compounds B1, C2 and C4 did not show P. aeruginosa antifilm activity, with the exception of compound C1, which had an effect on the Pa06 strain. The activity of antitumor activity resulted in values ranging from 85.06% - 24.1% for compound B1 and 73,56% - 27,59% for compound B2, indicating a possible antitumor activity. Toxicity screening of chalconity results revealed toxicity against Artemia Salina.
Synthesis, characterization and evaluation of the biological activity of Fluorinated Chalcone derivatives
Keywords: Chalconas sintéticas; Atividade antitumoral; Pseudomonas aeruginosa; Novos fármacos; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; MICROBIOLOGIA APLICADA::MICROBIOLOGIA MEDICA